The Influence of Green Marketing Campaign, Sustainability Commitment, and Community-Based Marketing on Brand Preference in Bandung FMCG Sector - Frans Sudirjo; Sudarsono Sudarsono; Usup Usup (Westscience Press, 2025)
This study investigates the influence of Green Marketing Campaigns, Sustainability Commitments, and Community-Based Marketing on Brand Preference in the FMCG sector in Bandung, using a quantitative analysis approach. Data were collected from 150 respondents using a Likert scale (1-5) and analyzed with SEM-PLS 3. The results reveal that all three variables significantly impact Brand Preference, with Community-Based Marketing showing the strongest effect. Green Marketing Campaigns and Sustainability Commitments also demonstrate substantial positive influences. These findings highlight the growing consumer preference for brands that prioritize environmental responsibility, sustainability, and community engagement. Practical implications include the need for FMCG companies to integrate these elements into their marketing strategies to enhance consumer loyalty and brand positioning.